Postmenopausal women in gynecological care - Pertyńska-Marczewska, Magdalena; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2021)
Menopause is one of the most important events in the female reproductive life cycle, being a transition from the reproductive to the nonreproductive stage. It is a milestone that may have a negative influence on quality of life and one that brings in several physiological changes that affect the life of a woman permanently. According to a Polish epidemiological forecast, in 2050 the average female life expectancy will be 87.5, which is 6.4 years longer than today. Thus, the life expectancy of women who will be 60 or older in 2050 will also extend. Therefore, strategies need to be optimized to maintain postreproductive health, in part because of increased longevity. The general gynecologist can expect to see more elderly female patients as the population continues to age. Office management of the gynecologic problems of geriatric women requires sensitivity to the special needs of this group. Nowadays, most women spend more than one-third of their lives after menopause; therefore there is plenty of opportunity for gynecologists to cater to the needs of postmenopausal women. It is in their scope of practice to help postmenopausal women through “healthy aging”. In this review we look into screenings, early identification, lifestyle modifications and appropriate intervention that may prevent many chronic conditions that cause morbidity and mortality during the postmenopausal years.